2013
DOI: 10.1021/ic401125e
|View full text |Cite
|
Sign up to set email alerts
|

Mo- and W-Based Organic Nanostructures Prepared from Bulk Crystal Isomorphs Consisted of [(CH3CH2)3NH)]2[MO2(C14H6O4)2] (M = Mo, W)

Abstract: Two new crystal isomorphs consisting of complexes [(CH3CH2)3NH)]2[MoO2(C14H6O4)2] (1) and [(CH3CH2)3NH)]2[WO2(C14H6O4)2] (2) have been synthesized, respectively, and from which Mo-based flexible and durable nanopipes with diameters of 16 nm and lengths of hundreds of micrometers and W-based rigid and fragile nanotubules with ununiform diameters ranging from 30 to 100 nm and lengths in tens of micrometers have been prepared separately, which revealed that the change of the metal in the coordination center of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…On the basis of that the contrast of the shapes of nanostructures on TEM image is associated with the electron densities of the nanosubstance, whereas the electrons of Mo atom are only a half of those of W; molybdenum complexes are easier to assemble into a one-dimensional structure than its tungsten isomorphs, 16 and the same kind of complexes with same bond lengths and angles prefer to aggregate together, similar to the saying that birds of the same feather flock together; it is suggested that the pale one-dimensional nanowires are assembled by [(CH 3 . To reveal the mechanism of the formation of the Mo−W-mixed nanostructures, we determined the bulk single Mo−W-mixed crystal structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of that the contrast of the shapes of nanostructures on TEM image is associated with the electron densities of the nanosubstance, whereas the electrons of Mo atom are only a half of those of W; molybdenum complexes are easier to assemble into a one-dimensional structure than its tungsten isomorphs, 16 and the same kind of complexes with same bond lengths and angles prefer to aggregate together, similar to the saying that birds of the same feather flock together; it is suggested that the pale one-dimensional nanowires are assembled by [(CH 3 . To reveal the mechanism of the formation of the Mo−W-mixed nanostructures, we determined the bulk single Mo−W-mixed crystal structure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Also we have synthesized two new isomorphic crystals consisting of [(CH 3 CH 2 ) 3 NH)] 2 -[MO 2 (C 14 H 6 O 4 ) 2 ] (M is Mo or W), from which we prepared two noticeably different Mo-and W-based nanostructures and revealed the mechanism that caused the differences between the Mo-and W-based nanostructures. 16 Herein, we synthesize the Mo−W-mixed bulk single crystal consisting of [(CH 3 CH 2 ) 3 NH)] 2 [Mo 0.75 W 0.25 O 2 (C 14 H 6 O 4 ) 2 ], for the improvement of the metal organic nanomaterials in structures and physical properties because usually Mo is mixed with W into a bialloy for better application in industry. Also we prepared Mo−W-mixed nanotubes which possess the features of both the Mo-and W-based nanomaterials from the Mo−Wmixed bulk crystal.…”
mentioning
confidence: 99%
“…[20][21][22][23][24][25][26] By grinding and ultrasonication, we disassemble the single crystals into nanostructures with varieties of morphologies, such as nanowires, nanoparticles, nano-tubules and nano-ribbons. Espe-cially, we have prepared different nanostructures from bulk crystals [ [28] , that combined with protonated 1,2-DPA, and demonstrated that the morphologies of the nano-aggregates are associated with the quantum motifs in their crystal lattices; for instance, the quantum-spots induced the formation of nanoparticles, quantum-wire lured the production of nano-ribbons, etc.…”
Section: Scheme 1 Schematic Presentation Of Bulk Crystal With 2d-flamentioning
confidence: 99%
“…Due to their superior optical, electronic, and magnetic properties, one-to three-dimensional W-based organic-inorganic hybrid materials have received extensive attention and have been synthesized by hydrothermal/solvothermal methods [20][21][22], among which the intercalation method is most widely used [22]. However, the above methods involve a high reaction temperature, a long reaction time, or the use of WCl 6 [W(CO) 6 ] as the W precursor [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the above methods involve a high reaction temperature, a long reaction time, or the use of WCl 6 [W(CO) 6 ] as the W precursor [20,21].…”
Section: Introductionmentioning
confidence: 99%